Fantastic 4R dalam Dental Radiografi Waste Management: Short Comunication - Azhari; Ivhatry Rizky; Suhardjo; Lutfi Yondri (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2022)
Environment-friendly health based welfare is the basis for created dental health services. Waste generated in dental health services, especially in effluent dental radiography can have a significant impact on environmental pollution and increase pollution. Fantastic 4R (re-think, reduce, re-use, recycle) is an effluent waste material efficiency that can reduce costs, time and energy as well as innovative innovations in their recycling. Fantastic 4R aims to create an eco-friendly green dentistry to realize a healthy environmental quality, be it physical, chemical, biological, or social that allows for the health degree of human resources. Efforts to "Green" both practitioners, governments and patients are a form of implementation of new strategies that lead to eco-consiousness that supports and maintains health. Together in realizing "go green" and protect the earth from environmental pollution for a better future.